Factors Related to Clinical Outcome of Patients with Stroke and COVID-19 Pneumonia in Dr. Mohammad Hoesin General Hospital Palembang - Masita; Pinto Destiramadhoni Ramadhoni; Ika Erna Uli Sirait (Jurnal RSMH Palembang, 2022)
COVID-19 infection may predispose thrombotic complications mediated by inflammation, endothelial dysfunction, and platelet activation. Several studies have reported that infection with COVID-19 is associated with both ischemic and hemorrhagic stroke. Stroke with COVID-19 Pneumonia is associated with increased morbidity and mortality. This study aimed to describe factors related to clinical outcomes in stroke patients comorbid with COVID-19 pneumonia. This study was an observational study with a cross-section approach. The population of this study is the medical records of stroke patients with pneumonia due to COVID-19 who were treated at Dr. Mohammad Hoesin General Hospital Palembang. Sample inclusion criteria in the form of medical record data for stroke patients with COVID-19 pneumonia and treated from January to June 2021. It was found that the most demographic characteristics were age (30-60 years), female, and comorbid hypertension. The most clinical characteristics were hemorrhagic stroke with severe NIHSS category and hypercoagulable conditions, and respiratory failure. From the bivariate analysis, it was found that the use of a ventilator was significantly associated with the incidence of death from stroke with COVID-19 pneumonia.